การศึกษาการใช้วัสดุธรรมชาติในการสร้างงานศิลปะของนักเรียนชั้นประถมศึกษาปีที่ 3 ในโรงเรียนประถมศึกษา สังกัดกรุงเทพมหานคร - นราพงศ์ แก้วท่าไม้ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research was to study the utilization of natural materials to create artwork of third grade students in schools under Bangkok metropolitan administration. The samples of this study were 400 students, 50 art teachers and 8 art educators. The instruments used in this research were the questionnaire and the interview form. The collected data were analysed by means of percentage, arithmetic mean, and standard deviation. Content analysis technique was used. The result of the research were found that 1. Using of natural materials in creating art works of primary students (year 3). According to student’s opinion: - Design: (student s agreement level) [X-bar] = 3.81 - Planning (student s agreement level) [X-bar] = 3.84 - Materials & Equipment: (student s agreement level [X-bar] = 3.92 - Methodology: ( student s agreement level) [X-bar] = 4.18 2. Using of natural materials in creating art works of primary students (year 3). According to Art Teacher s opinion: - Design: (Art teacher’s agreement level) [X-bar] = 3.85 - Planning: (Art teacher s agreement level) [X-bar] = 3.30 - Materials & Equipments: (Art teacher s agreement level) [X-bar] = 4.00 - Methodology: (Art teacher s agreement level) [X-bar] = 3.76 3. Suggestions of art teachers 3.1 Using natural materials in creating artwork of students is very important as it helps students to develop their ideas, imagination, and working process as well as characteristic and allow them to understand benefits of using natural resources and environment. 3.2 Children should have good awareness and teachers should develop students good sense of caring environment and natural resources by providing variety of samples to motivate students creativity. 3.3 Students should learn how to use natural materials valuable to increase and apply more natural resources knowledge to their artworks. 3.4 Students should be encouraged to increase and apply more natural resources knowledge to their artworks. 4. Points of view of Expertise in teaching art education 4.1 Design: Students should learn the basic elements of art, how to look, notice and plan in prior to the job. Hence, students will enable to learn and face with any problems from their own experience. 4.2 Planning: In teaching planning, students should be emphasized on planning prior to implementation of a project with supervision of the teacher. 4.3 Materials & Equipments: Students should realize the advantages of materials from natural resources and the environment. Teacher should encourage students to explore and experiment on diversity and choice in natural resources to make inventive artwork. 4.4 Working process: Students should follow working process to reach the objectives under supervision of teachers. Activities should be organized to correspond with students cognitive development.